The influence of Со2+ low doses in vivo prolonged administration on the erythrocytes hemolysis - Сі, У; Корнієнко, Є. М.; Плотніков, А. Д.; Пиріна, І. С.; Кот, К. В.; Кот, Ю. Г.; Перський, Є. Е. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The effect of intragastric injection of Co2+ in doses of 0.012 and 0.06 mg/kg/day for 15 and 36 days on the hemolysis of 3-month-old Wistar rats red blood cells by the action of HCl has been studied. The animals were divided into 5 groups. Group 1 – the control – the animals got clean water for 36 days, in groups 2 and 3 – CoCl2 solutions in the above-mentioned doses for 15 days, and in groups 4 and 5 – these solutions for 36 days. Water and salt solutions were administered by intragastric gavage daily. Erythrocytes were obtained from whole blood of rats. Hemolysis induced by the addition of HCl to its final concentration of 0,002 N. Erythrocyte hemolysis kinetics was recorded by changes in the optical density of samples with registration step of 1 s. The time of red blood cells membrane restructuring before beginning the process of their destruction and the rate of its destruction were selected as indicators of hemolysis. It has been shown that cobalt ions provide additional destabilizing effect on the erythrocyte membrane. This effect increases with the dose of Co2+ and the duration of its administration.